THE ROLE OF IBRAHIM DAVRON IN THE DEVELOPMENT OF THE JADID PRESS - Kodirova Muhayyoxon Soliyevna,Kurbonova Feruza A’zamovna (International Journal of Literature and Language Studies, 2026)
Ibrahim Davron occupies an important place in the history of our literature as a skilled publicist. This person, who was a contemporary writer of his time, responded to the most urgent problems in the life of the society. He ruthlessly criticized the shortcomings encountered in life. From his point of view, he focused on nothing - defects in schools and education, incompetence of teachers, carelessness of some people to the life and fate of the nation, heresy and superstitions, whatever was relevant, and as a representative of this nation, he expressed his views and opinions. stated. With the high level of his journalistic articles, the importance of the raised issues, the vividness and vitality of the narrative method, he can easily compete with the journalism of his pen brothers Behbudi, Fitrat, Cholpon, Hamza, Avloni.